Marx e Piaget: aproximações teóricas e epistemológicas - Dongo-montoya, Adrian Oscar (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2018)
Abstract: The present paper aims at showing the closeness between Piaget’s and Marx’s thoughts concerning basic theory and epistemology issues of sociological research. Specifically, about the way both authors study the relation between these parts and the whole social aspects, the relation between the material action and social representation, the relation between sync and diachrony and finally the relation between scientific and ideological activities. In such perspective, it will be analyzed Piaget’s studies regarding sociology and his agreement points with Marx’s thesis. The results of such research prove the existence of real nearness between both thoughts and what was analyzed.

Este estudo propõe mostrar as aproximações do pensamento de Piaget com o de Marx em função da pesquisa sociológica de ambos os autores. Essas aproximações se manifestam nisto: as relações entre as partes e o todo societário, as relações entre a ação material e as representações sociais, as relações entre a sincronia e a diacronia e o papel das centrações e descentrações na formação das representações individuais e coletivas. Nessa perspectiva, analisaremos principalmente os estudos de Piaget sobre tais questões. Não deixaremos de analisar alguns estudos do próprio Marx e de seus seguidores sobre questões análogas, a fim de verificar supostas aproximações. Os resultados da nossa pesquisa evidenciam aproximações teóricas entre ambos os autores.
Marx and Piaget: theoretical and epistemological approaches
Keywords: Piaget’s Thought; Marx’s Thought; Action and Representation; Synchrony and Diachrony; Science and Ideology; Pensamento de Piaget; Pensamento de Marx; Ação e Representação; Sincronia e Diacronia; Ciência e Ideologia